Why Do Women Underestimate the Risk of Cardiac Disease? A literature review - Hammond, J.; Salamonson, Y.; Davidson, Patricia; Everett, B.; Andrew, S. (Elsevier Inc, 2007)
Background: Despite the quantity of information available to women about risk factors for cardiovascular disease (CVD), many women do not perceive this risk. Aim: This paper seeks to identify factors in the published literature that influence women's risk perception of heart disease, and how these perceptions influence health outcomes. Method: A literature search from 1985 to 2006 using the CINAHL, Medline, Embase and PsycINFO electronic databases was undertaken. The keywords used were "perceived risk", "cardiac isk factors", cardiovascular disease", risk misconception", and "heart disease", combined with "somen" and/or "gender". Additional data was obtained by manual searches of bibliographies of articles identified in the electronic searches, and internet searches. Findings: Until the late 1980s, CVD was perceived as a disease which primarily affected men, as few large clinical trials recruited women. This resulted in a lack of data documenting the relationship between known risk factors and gender. Until recently, health professionals have not focused on disseminating gender-specific information about CVD risks to women, causing women to underestimate their risk of developing CVD even when risk factors are clearly evident. Furthermore, women are less likely than men to recognise the signs and symptoms of CVD, delay in seeking treatment, and fail to adopt healthy lifestyles, all of which increase the incidence of mortality and morbidity in a disease that is largely preventable. Conclusion: This review highlights the need for health professionals to "bridge the gap" between perceived and actual risk of CVD in women, and to develop educational programs that specifically target women.